2010
DOI: 10.1111/j.1439-0418.2009.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of ants (Hymenoptera: Formicidae), vine mealybugs and mealybug parasitoids in vineyards

Abstract: The mutualistic association between some ant species and honeydew‐producing Hemiptera has been shown to influence the distribution patterns and abundance of these hemipterans and their natural enemies. We studied the spatial distribution patterns of three ant species, mealybugs and mealybug parasitoids for two consecutive growing seasons on three wine grape farms in the Western Cape, South Africa. During the study period, no ant or mealybug controls were applied. Ant and mealybug monitoring was conducted on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 35 publications
0
35
2
Order By: Relevance
“…Despite the negative effect of semi‐natural habitats, infestations by mealybugs were always greater in organic than in conventional vineyards suggesting that organic vineyards could be highly beneficial to mealybugs. Indeed, mealybugs are favoured by the tillage, the presence of Formicidae and a decreased exposure to synthetic pesticides (Daane et al., ; Mgocheki & Addison, ; Muscas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the negative effect of semi‐natural habitats, infestations by mealybugs were always greater in organic than in conventional vineyards suggesting that organic vineyards could be highly beneficial to mealybugs. Indeed, mealybugs are favoured by the tillage, the presence of Formicidae and a decreased exposure to synthetic pesticides (Daane et al., ; Mgocheki & Addison, ; Muscas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ant species Anoplolepis steingroeveri (Forel) and Iridomyrmex spp. did not show a significant impact on entomophagous insects in vineyards . Crucially, depending on the sugar and protein availability and the nutritional requirements of the ant colony, ants may also prey on the mealybugs …”
Section: Introductionmentioning
confidence: 90%
“…The degree of protection depends on several factors such as ant species, abundance and quality of honeydew, as well as, on the availability of alternative food for the ants . Some species, such as Linepitema humile (Mayr) and Crematogaster peringueyi Emery, reduce the efficacy of natural enemies in vineyards, including those of the vine mealybug . More recently, it was shown that the ant Tapinoma nigerrimum (Nylander) significantly disrupted either the parasitism potential or the predatory activity of main vine mealybug's natural enemies occurring in Mediterranean vineyards .…”
Section: Introductionmentioning
confidence: 99%
“…Mealybugs are one of the most important pests in vineyards (Daane et al, 2008) and ants are strongly associated with them. The invasive Argentine ant, Linepithema humile (Mayr) was associated with higher mealybug densities and fruit infestation in California (Daane et al, 2007) and South Africa vineyards (Mgocheki & Addison, 2010). Moreover, ants have been found to induce populations increases of pests that do not produce honeydew, such as Aonidiella citrina Craw (Hemiptera: Diaspididae) (Flanders, 1945), Aonidiella aurantii Murdoch (Hemiptera: Diaspididae) Pekas et al, 2010b;Dao et al, 2014) and Panonychus citri (McGregor) (Acari:…”
Section: Ants In Agricultural Ecosystemsmentioning
confidence: 99%
“…It is typically assumed that ants obtain honeydew, a food source that is copious, nutritive and spatiotemporally constant and in exchange, ants protect the honeydew producers from their natural enemies or other competing herbivores (Flanders, 1951;Bartlett, 1961;Way, 1963;Buckley, 1987;Rosumek et al, 2009 (Flanders, 1951;Bach, 1991;Itioka & Inoue, 1996a;James, 1997;Daane et al, 2007;Mgocheki & Addison, 2010). In citrus crops, Moreno et al (1987) reported that the exclusion of the Argentine ant Linepithema humile (Mayr) was associated with lower densities of the citrus mealybug Planococcus citri Risso (Hemiptera: Pseudococcidae) and of the woolly whitefly Aleurothrixus floccosus Maskell (Hemiptera:…”
Section: Introductionmentioning
confidence: 99%